In situ electrochemical microcantilever bending test: A new insight into hydrogen enhanced cracking. (15th April 2017) - Hajilou, Tarlan; Deng, Yun; Rogne, Bjørn Rune; Kheradmand, Nousha; Barnoush, Afrooz
Abstract: Single crystalline microcantilevers of Fe–3wt% Si were bent while electrochemically hydrogen (H) charged in situ inside a miniaturized electrochemical cell and are compared with cantilevers bent in air. Yield point decreases, crack initiation and propagation were observed for the cantilevers bent in the presence of H, while notch blunting occurred for the cantilevers bent in air. The results show H enhanced dislocation nucleation and H pinning of dislocation at the crack tip are responsible for embrittlement. Graphical Abstract: